Hyperidentities with permutations in invertible binary algebras - Shahnazaryan, Davit; Davidov, Sergey (Armenian Journal of Mathematics, 2022)
In this paper, using hyperidentities with permutations we obtained characterization invertible algebras of various types of linearity.